Foundation for a national road prioritisation model for South Africa - Townshend, Matthew John (School of Economics, 2020)
Inefficient road infrastructure investment in South Africa has led to five core policy failures: deterioration in road network conditions; neglect of citizens' constitutional rights of access to basic services; insufficient prioritisation of roads that best promote the general economy; an excessive rural road network; and application of inefficient road surfaces that increase road maintenance and road-user costs and fail to take advantage of the low shadow price of unskilled labour. The thesis first reviews the extent and consequences of these failures and evaluates their opportunity cost with respect to the potential benefits from more efficient road infrastructure investment policy. If fiscal constraints are accepted as exogenous given South Africa's politically driven budgeting process and the magnitude of road maintenance backlogs, then the question can be posed as to the capacity of the current maintenance scheduling systems to efficiently prioritise road investment according to the sector mandate to (i) satisfy citizens' right of access to constitutionally protected basic services, and (ii) maximally contribute to economic growth. The answer to this question is negative: the fact that none of the systems are appropriate to prioritisation explains the identified core failures. The thesis addresses this gap in several stages of analysis. The first stage is to develop a cost-effectiveness analysis-based road classification system that accounts for basic access and economic growth. This generates two important findings: most of the demand for access to basic services, which as per a normative economic framework based on arguments due to Rawls and Binmore is the first lexicographical policy priority, can be satisfied by roads that also support economic growth; and authorities can maintain Basic Access Roads and still have significant fiscal space within current allocations to maintain roads that optimally contribute to economic growth. The optimisation exercise proceeds through three stages. First, lifecycle cost analysis is applied to determine cost-effective surface solutions for low volume roads, many of which are Basic Access Roads, and the employment benefits of a policy to seal low-volume roads. Second, a two-step floating catchment area model is used to identify potentially unproductive roads that may be cost-effectively rationalised through basic service hub relocation. With basic access rights satisfied efficiently, cost-effectiveness analysis is lastly applied to exploit the remaining exogenously given road budget allocation to develop and test a model of road maintenance prioritisation that optimises the sector's contribution to national economic growth via export promotion, which is identified in official literature as the primary variable under policy control to promote national economic growth.